Constraining factors in the development of veterans’ track and field athletics movement in Russia and pathways to their elimination - Stolyar, L.M.; Stolyar, K.E.; Vitko, S.Yu.; Lubyshev, E.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify and systematise the main constraining factors in the development of the veterans’ track and field athletics movement in Russia and to outline pathways for their elimination. Methods and structure of the study. The work employed a range of methods: analysis and synthesis of scientific-methodological literature and official sources (records of international and national competitions, regulatory legal acts), analysis of statistical materials, and secondary analysis of sociological surveys of veteran athletes (n>100) conducted in 2020–2022. Results and conclusions. Despite record figures for Russia in certain events (over 700 participants in Saint Petersburg in 2025), the overall scale of the movement remains at the level of stagnation. The necessity of removing the identified barriers is substantiated in order to realise the achievement-oriented and socio-communicative potential of veteran athletes as an important factor in active longevity and social stability.